Validation of a visual analogue scale for the evaluation of the postoperative anxiety: A prospective observational study - François Labaste; Fabrice Ferré; Hélène Combelles; Valentin Rey; Jean‐Christophe Foissac; Anne Senechal; Jean‐Marie Conil; Vincent Minville (Wiley, 2019)
Abstract Aim Anxiety affects the perception of pain during the postoperative period. A simple evaluation scale could improve the management of this component. The objective of this study was to evaluate the reproducibility and the consistency of a visual analogue scale for anxiety compared with the reference method, the State‐Trait Anxiety Inventory (STAI). Design Observational, prospective, monocentric study of 500 patients in the post‐anaesthetist care unit. Anxiety was evaluated using both the visual analogue scale for anxiety and the STAI in perioperative patients. Consistency between the visual analogue scale for anxiety and the STAI, detection thresholds and factors predicting anxiety were researched. Results A correlation was found between the visual analogue scale for anxiety and the STAI. There was also a correlation between pain and anxiety. Analysis of receiver operating characteristic (ROC) curves showed a visual analogue scale for anxiety threshold of 34/100 allowing the identification of patients with or without anxiety. Predictive factors for anxiety are female gender, use of benzodiazepine in premedication, emergency surgery and significant pain in the post‐anaesthetist care unit. In summary, visual analogue scale for anxiety is a useful tool for detecting the anxiety component of postoperative pain. It could be used in association with covariates of interest to improve anxiety management during the postoperative period.